Consumption symbolism on Chritmas products and activities a case study of adolescents in Cabatuan, Iloilo, Philippines. - Pormon, Janzen S.
A case study aims to describe the process of consumption symbolism manifested in the adolescent homogeneous dyad groups through the interplay of encoding and decoding of meanings attached to the 2013 Christmas acquisitions. The dyads were teenage and secondary level students of Cabatuan National Comprehensive High School in Cabatuan, Iloilo. Since sex differences were observed, ten (10) pairs of male homogeneous dyads and another ten (10) pars of female homogeneous dyads were subjected to interview process where a one on one interview is conducted to each adolescent to lessen sharing of symbols and meanings. The results revealed five categories of products which are fashion, accessories, gadgets, consumable, and souvenirs as well as three categories of activities, religious, quality time and grooming. Further, the interplay of encoding and decoding of consumption symbols of the dyads involves four stages; the consumption, recognition of consumption, approval of the consumption, and sharing meaning over the consumption. The process of consumption symbolism among the dyads requires all these stages in order to exhibit consumption symbolism. Lastly, male homogeneous dyads are likely to exhibit consumption symbolism on quality time activities while both fashion products and quality time activities to female homogeneous dyads.